Designation of Land for Expropriation and Compensation for Property Rights in the Construction of the Semarang-Demak Toll Road - Syaiful Ihsan Hilmi (Universitas Negeri Semarang, 2026)
This study aims to analyze the parameters for designating land as expropriated and the mechanisms for providing compensation for community property rights in the construction of the Semarang-Demak Toll Road. The main issue arises when land that still holds economic value for residents is designated as expropriated, resulting in compensation shifting from conventional compensation to a Goodwill Fund, which is considered to offer insufficient legal certainty. The research method employed is a legal-empirical approach using a case study methodology. Primary data was collected through field interviews, while secondary data includes primary, secondary, and tertiary legal materials analyzed using descriptive qualitative methods. The findings indicate that the designation of land as “expropriated” is based on cumulative parameters: changes in physical form, the loss of land boundaries, and the total loss of the land’s economic function. The regulatory transformation from Presidential Regulation No. 52 of 2022 to Presidential Regulation No. 27 of 2023 marks a significant paradigm shift, wherein the assessment of the Compensatory Fund is now professionally conducted by the Public Appraisal Services Office (KJPP) using the income capitalization method. Although land rights are legally and formally extinguished under the UUPA, the provision of the Redress Fund continues to be implemented as a social policy instrument reflecting the principle of distributive justice for affected groups. In conclusion, the effectiveness of this policy requires inter-agency collaboration through an Integrated Team as well as a more comprehensive legal reformulation to ensure that the protection of citizens’ economic rights remains safeguarded within National Strategic Projects.